Is a cardiac catheterization procedure at hospitals without on-site surgical backup safe? - Regmi, S R; Dhital, B M; Sharma, B (Journal of Chitwan Medical College, 2017)
Percutaneous cardiac catheterization procedures have now become an established and preferable method. Initially, these procedures were performed at clinical sites with surgical backup as complication rates and need of urgent surgery were high. With the improvement in catheter technique, experienced operators and the development of new devices, overall complication rates of catheterization are low and emergency cardiac surgery has become an increasingly rare event. The aim of the study was to evaluate the procedural outcomes for cardiac interventions in a tertiary-level hospital without onsite cardiac surgery backup. This was a prospective descriptive study. All consecutive patients who were admitted for percutaneous cardiac interventions, including both diagnostic as well as therapeutic interventions, between September 2013 and August 2015 were included in this study. Total 692 percutaneous cardiac interventions were performed. The mean age was 61.9 ± 18.3 years. 439(63.52%) procedures were carried out in men. PCI was done in 189(27 .31%). Percuteneous transvenous mitral comissurotomy was done in 49(7.08%) cases, coronary angiogram was done in 395(57.08%), permanent pacemaker insertion in 29(4.20%), peripheral angiogram in 16(2.30%), pericardiocentesis in 14(2 .02%).Primary PCI was done in 62(32.88%). The most frequent indication for PCI was STEMI 106(56.16%). Complications like Post-procedural cardiogenic shock in 4 (2.11%) cases, arrhythmias and minor complications in 7 (3.70%), and death in 4 (2.11%) patients was witnessed. Similarly, periprocedural MI and contrast induced nephropathy (CIN) requiring dialysis stroke or transient ischemic attack were not noted.Cardiac tamponade was observed in 1 (2.02%) patient during PTMC. There was no need of emergency cardiac surgery Percutaneous cardiac intervention was feasible with acceptable complications in a tertiary-level hospital without onsite cardiac surgery backup.